2018
DOI: 10.15560/14.6.1017
|View full text |Cite
|
Sign up to set email alerts
|

First record of Steindachnerina insculpta (Fernández-Yépez, 1948) (Characiformes, Curimatidae) in Argentina

Abstract: Recent expeditions to northwestern Argentina revealed the presence of an unknown species of Curimatidae for the Bermejo river basin. The morphometric and meristic analyses of these specimens allow us to identify them as Steindachnerina insculpta (Fernández-Yépez, 1948), which is here reported for the first time in Argentina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…More recently, Koerber et al (2017:16) in the checklist of fishes from Paraguay cited S. brevipinna, S. conspersa and S. insculpta, the latter being S. nigrotaenia according to the concept herein established; they also erroneously refer to the type locality of S. insculpta as being in Venezuela, disregarding that Britski (1969:201), and Vari (1991:72) had already clarified this question. Aguilera et al (2018) also reported the first occurrence of S. insculpta in Argentina, which, based on their description, the species in question also represents S. nigrotaenia.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Koerber et al (2017:16) in the checklist of fishes from Paraguay cited S. brevipinna, S. conspersa and S. insculpta, the latter being S. nigrotaenia according to the concept herein established; they also erroneously refer to the type locality of S. insculpta as being in Venezuela, disregarding that Britski (1969:201), and Vari (1991:72) had already clarified this question. Aguilera et al (2018) also reported the first occurrence of S. insculpta in Argentina, which, based on their description, the species in question also represents S. nigrotaenia.…”
Section: Discussionmentioning
confidence: 99%